THE RESOLUTION OF THE CONGRESS OF PEDIATRICIANS OF RUSSIA «ACTUAL PROBLEMS IN PEDIATRICS» - A.A. Author ("Paediatrician" Publishers LLC, 2007)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2007;6(2):156-159)